Preoperative prediction for early recurrence of hepatocellular carcinoma using machine learning-based radiomics - Mao, Bing; Ren, Yajun; Yu, Xuan; Liang, Xinliang; Ding, Xiangming (Frontiers in Oncology, 2024)
Objective To develop a contrast-enhanced computed tomography (CECT) based radiomics model using machine learning method and assess its ability of preoperative prediction for the early recurrence of hepatocellular carcinoma (HCC).Methods A total of 297 patients confirmed with HCC were assigned to the training dataset and test dataset based on the 8:2 ratio, and the follow-up period of the patients was from May 2012 to July 2017. The lesion sites were manually segmented using ITK-SNAP, and the pyradiomics platform was applied to extract radiomic features. We established the machine learning model to predict the early recurrence of all patients included in the study were followed up for over 1 year.